Survey on Gendered Constraints to Employment and Entrepreneurship, Lesotho - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
The dataset comprises a sample of small and medium-sized enterprises in Lesotho interviewed in 2021. The sectors represented are farms; agro-processors; other agricultural businesses; manufacturers; tourism industries & creative industries. The survey instrument was designed to capture information on the experiences of and constraints to employment and entrepreneurship among under-represented groups, specifically: women, youth & persons with disabilities.